REVITALISASI HUBUNGAN SOSIAL TENAGA KEPENDIDIKAN MELALUI PEMANFAATAN MEDIA DIGITAL SEKOLAH - Ana Azhari (Hijri, 2025)
This study aims to analyze the strategy of utilizing digital media in revitalizing the social relations of education personnel. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman interactive model. This study involved one key informant and nine supporting informants from various roles in educational institutions. The results of the study indicate that digital media can improve the quality of social relations when used interactively, personally, and with an emotional touch. This media not only functions as a means of conveying information, but also as a tool to strengthen collaboration between work units and build closer social connections if utilized with an empathetic approach. Two-way communication, shared moral support, and involvement in non-formal conversations through digital platforms have been shown to increase solidarity and a sense of belonging among education personnel. The contribution of this study is the accuracy of digital media, when used consciously and with attention to the emotional and humanitarian dimensions, can be an important bridge in building harmonious social relations in the educational environment.Keywords: Digital media, Social relations, Education personnel, Revitalization